Effects of SDF-1/CXCR7 on the Migration, Invasion and Epithelial-Mesenchymal Transition of Gastric Cancer Cells - Shi, Ameng; Wang, Ting; Jia, Miao; Dong, Lei; Shi, Haitao (Frontiers in Genetics, 2021)
We found that SDF-1/CXCR7 axis plays an important role in the growth and proliferation of gastric cancer in previous studies. The objectives of this study were to explore the effects of SDF-1/CXCR7 on the metastatic ability of gastric cancer cells and the possible mechanisms. SGC-7901 gastric cancer cells were cultured in vitro, CXCR7 expression was stably knocked down via lentiviral vectors. The cell migration and invasion abilities were detected by transwell migration and invasion assays. The expression of matrix metalloproteinase 2 (MMP-2), MMP-9, vascular endothelial growth factor (VEGF), epithelial-mesenchymal transition (EMT) markers and Akt phosphorylation were detected with western blot. We found that SDF-1 markedly enhanced the migration and invasion abilities of SGC-7901 gastric cancer cells; CXCR7 knockdown by lentiviral infection inhibited these effects. SDF-1/CXCR7 increased the expression of MMP-2, MMP-9 and VEGF. SDF-1/CXCR7 also downregulated E-cadherin expression but upregulated N-cadherin, vimentin and Snail expression, suggesting that SDF-1/CXCR7 could promote the development of EMT in gastric cancer cells. Furthermore, SDF-1/CXCR7 could promote Akt phosphorylation. Our results indicated that SDF-1/CXCR7 promoted the migration, invasion and EMT of gastric cancer cells and thus CXCR7 inhibition may be a strategy for inhibiting gastric cancer metastasis.